EFICACIA PRECLÍNICA Y CLÍNICA DE LA CURCUMINA COMO AGENTE ANTIINFLAMATORIO PARA LA PERIODONTITIS. UNA REVISIÓN SISTEMÁTICA - Ridho, Fiki Muhammad (2024)
Introduction: There is ongoing exploration into herbal treatments to identify adjunct therapies with minimal side effects. One such treatment involves curcumin from turmeric (Curcuma longa). This study aims to review the efficacy of curcumin as an anti-inflammatory agent for periodontitis along with the mechanisms of action involved. Methods: A systematic review of pre-clinical and clinical studies published on Scopus, PubMed, ScienceDirect, and Google Scholar up to May 2024 was employed following the PRISMA guidelines. Three tools were used for risk of bias assessment, namely the QUIN tool for in vitro studies, the SYRCLE’s RoB for in vivo studies, and the Cochrane RoB 2 for RCTs. Finally, nineteen studies were included for review. Results: This study highlights curcumin’s efficacy in addressing periodontitis through diverse mechanisms. Curcumin demonstrated efficacy in attenuating inflammation within periodontal tissue by inhibiting several pro-inflammatory cytokines and mediators such as interleukin (IL)-1, IL-6, tumor necrosis factor (TNF)-α, matrix metalloproteinases (MMPs), prostaglandin E2 (PGE2), cyclooxygenase (COX)-2, while concurrently increasing IL-4 and IL-10. In addition, several transcription factors such as nuclear factor-kappa B (NF-κB) and signal transducer and activator of transcription 1 (STAT1) were also inhibited by curcumin. Administration of curcumin has additionally been demonstrated to reduce other biomarkers of periodontitis, including C-reactive protein (CRP), alkaline phosphatase (ALP), and procalcitonin (PCT). Conclusion: Curcumin has been shown to be effective as an adjunct therapeutic agent for periodontitis due to its anti-inflammatory effects by reducing the inflammatory response through a diverse range of mechanisms of action.